The effects of psychological safety and employee voice behavior on flight attendants’ mindful safety practices adoption - Hu, Shi; Nadeem, Muhammad Aamir; Luo, Ji; Yi, Xiaobo (Frontiers in Public Health, 2024)
Flight attendants as the front-line staff in the cabin play a crucial role in air travel safety enhancement. This research aims to explore how psychological safety affects flight attendants' adoption of mindful safety practices through voice participation. This mechanism also identifies ethical leadership and traditionality as two moderators. A self-reported questionnaire was used to collect data from 621 flight attendants in Chinese private commercial airline companies. PLS-SEM (partial least square structured equation modeling) is used to examine the hypotheses proposed in the present study. After data analysis, the results reveal that the underlying mechanism covering mediating and moderating effects through which flight attendants' voluntary and extra-role safety behavior could be improved. The findings enhance the existing literature regarding the antecedents of flight attendants' mindful safety practices adoption. Managerial implications are also provided in the commercial aviation industry and discussed along with future research directions.